Association Between Serum Uric Acid to High-Density Lipoprotein Cholesterol Ratio and Pneumonia After Endovascular Treatment of Vertebrobasilar Artery Occlusion - Lan W; Yuan K; Xiao L; Qiu F; Sun W; Xu L; Cao H; Zhu W; Du M; Liu X (Journal of Inflammation Research)
Wenya Lan,1,2,* Kang Yuan,3,* Lulu Xiao,3 Feng Qiu,1 Wen Sun,4 Lili Xu,1 Hui Cao,1 Wusheng Zhu,3 Mingyang Du,1 Xinfeng Liu2 1Department of Cerebrovascular Disease Treatment Center, the Affiliated Brain Hospital of Nanjing Medical University, Nanjing Brain Hospital, Nanjing, People’s Republic of China; 2Department of Neurology, Affiliated Jinling Hospital, Nanjing Medical University, Nanjing, People’s Republic of China; 3Department of Neurology, Affiliated Jinling Hospital, Medical School of Nanjing University, Nanjing, 210002, People’s Republic of China; 4Stroke Center and Department of Neurology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingyang Du, Department of Cerebrovascular Disease treatment Center, the Affiliated Brain Hospital of Nanjing Medical University, Nanjing Brain Hospital, Nanjing, People’s Republic of China, Tel +862582296590, Email dmyang0128@126.com Xinfeng Liu, Department of Neurology, Jinling Hospital, Nanjing Medical University, No. 305 East Zhongshan Road, Nanjing, Jiangsu Province, 210000, People’s Republic of China, Tel +862584801861, Fax +862584805169, Email xfliu2@vip.163.comBackground: The uric acid to high-density lipoprotein cholesterol ratio (UHR) is a novel marker of inflammation and metabolism. We aimed to explore the association of UHR with pneumonia after endovascular thrombectomy (EVT) in patients with vertebrobasilar artery occlusion (VBAO).Methods: We retrospectively enrolled participants diagnosed with acute VBAO treated with EVT within 24 hours of estimated occlusion time from the multicenter PERSIST study. The primary outcome was pneumonia within 7 days after EVT according to the Pneumonia in Stroke Consensus Group recommendations. We utilized the restricted cubic spline curve to explore the dose–response relationship between UHR and pneumonia. We used multivariable logistic regression models to assess the association between UHR and the risk of pneumonia after EVT and verified the findings in subgroup analysis.Results: Three hundred and seventy-eight patients were enrolled in this study, and 236 (62.4%) were diagnosed with pneumonia. In multivariable models, a higher UHR was associated with an increased risk of pneumonia after EVT (odds ratio [OR], 1.05; 95% confidence interval [CI], 1.01– 1.10; P = 0.020; tertile 3 versus tertile 1: OR, 2.09; 95% CI, 1.15– 3.82; P = 0.016). The dose–response relationship indicated that UHR was linearly associated with the risk of pneumonia (P = 0.888). The association between UHR and pneumonia remained significant in different subgroups.Conclusion: This study demonstrated that a higher UHR was associated with an increased risk of pneumonia in VABO patients treated with EVT. Further studies were warranted to verify the prognostic values of UHR in pneumonia after EVT.Keywords: pneumonia, vertebrobasilar artery occlusion, stroke, thrombectomy, uric acid to high-density lipoprotein cholesterol ratio